Spirituality According to AQAL Model. A Contribution to Integral Education - Kielar, Marzanna Bogumiła (Przegląd Badań Edukacyjnych (Educational Studies Review), 2016)
The goal of the article is to analyse the phenomenon of spirituality with pointing to educational context. The question of spirituality was presented in the light of the AQAL integral meta-model. This model allows fordescribing spirituality as an internal and external dimension of existence, as levels of spiritual development, spiritual intelligence, spiritual states and types of spiritual experiences. The core issue of the AQAL model is an inclusive meta-theory on the one hand, and on the other, it is a series of inclusive practices. The results of the analysis can contribute to developing the spiritual aspect of human experience in thepractice of integral education.